Circular RNA WRNIP1 activates the PI3K-AKT and ERK1/2 signaling pathways by binding to miR-129-5p/IGF2 axis and facilitates ovarian follicle development in chickens - Xiyu Zhao; Yuanhang Wei; Xinyan Li; Xinghong Yu; Zhenyu Lei; Yao Zhang; Shunshun Han; Huadong Yin; Can Cui (Poultry Science, 2025)
The healthy and orderly development of ovarian follicles is the basic premise to maintain normal and continuous egg production of chickens. Emerging researches continue to reveal the crucial functions of circular RNAs (circRNAs) involved in follicle development. In the present study, a novel circular RNA WRNIP1 (circWRNIP1) with higher abundance in healthy follicles than in atretic follicles was identified, suggesting its important regulatory role in follicle selection and maturation. In this study, we demonstrate that circWRNIP1 promotes chicken ovarian follicle development by enhancing granulosa cell proliferation and inhibiting apoptosis. Furthermore, we validated the targeting relationships between circWRNIP1 and miR-129-5p, as well as between miR-129-5p and IGF2. Mechanistically, through co-transfection experiments, we show that circWRNIP1 activates the PI3K-AKT and ERK1/2 signaling pathways via the miR-129-5p/IGF2 axis. The present study provides new insights into the downstream molecular mechanism of circRNAs regulating follicle development, and is expected to provide reliable targets for the subsequent establishment of new molecular breeding strategies.